Pendampingan Penerbitan dan Penyiapan Akreditasi Nasional bagi Pengelola Jurnal Bidang Pengabdian kepada Masyarakat Perguruan Tinggi di Kota Semarang - Parmin; Stephani Diah Pamelasari; Endah Fitriani Rahayu; Aji Saputra (Jurnal Pemberdayaan Masyarakat, 2021)
Activities with service journal managers as research targets aim to increase managers' knowledge about management and journal articles' substance quality. Manager's knowledge which is the focus of activities, refers to the accreditation assessment of national journals. The main target of community service activities is the manager of the university service journal in Semarang. The method of mentoring activities is carried out online, divided into two forms: for management and article substance. Evaluation of activities was carried out through analysis of the value of pre-test and post-test questions on journal management and article substance and questionnaire analysis of participants' feedback. The average pre-test score is 65, and the post-test is 84, indicating an increase in knowledge on the target activities. From the mentoring in publishing service journals that have been carried out, the journal manager (the target of the activity) has had broader knowledge about the management and substance of the article. The accreditation simulation in the mentoring process has provided an authentic experience for managers to be more prepared to propose accreditation and reaccreditation of service journals.